2019
DOI: 10.4491/eer.2019.138
|View full text |Cite
|
Sign up to set email alerts
|

Application of feed-forward and recurrent neural network in modelling the adsorption of boron by amidoxime-modified poly(Acrylonitrile-co-Acrylic Acid)

Abstract: This research reports application of artificial neural network (ANN) in investigation and optimisation of boron adsorption capacity in aqueous solution using amidoxime-modified poly(acrylonitrile-<i>co</i>-acrylic acid) (AO-modified poly(AN-<i>co</i>-AA)). Both feed-forward and recurrent ANN have been utilized to predict the adsorption potential of synthesised polymer. Three operational parameters, which are adsorbent dosage, initial pH and initial boron concentration during adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The choice of delay range depends on the nature of the problem and the temporal dependencies in the data. Longer delay ranges can help the network capture longer-term dependencies but also increase model complexity and computational costs 40 . Shorter delay ranges may limit the network's ability to model longer-term dependencies.…”
Section: Results and Analysismentioning
confidence: 99%
“…The choice of delay range depends on the nature of the problem and the temporal dependencies in the data. Longer delay ranges can help the network capture longer-term dependencies but also increase model complexity and computational costs 40 . Shorter delay ranges may limit the network's ability to model longer-term dependencies.…”
Section: Results and Analysismentioning
confidence: 99%
“…In [32] it was observed that nodes centroids in an RBFN can be computed using some available clustering algorithms. Such an approach assumes that the internal configuration of the constructed RBFN is directly determined by the clustering algorithm outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This could be a disadvantage since centers are selected nonspecifically and the RBF performance relies critically on their location. To reduce the risk it was proposed to use the orthogonal least square algorithm, where the RBFN structure can be dynamically changed by adding a new neuron in the hidden layer [32].…”
Section: Introductionmentioning
confidence: 99%